Development of expert systems of ecological monitoring of Republic of Daghestan with use of adaptive semantic models - N. O. Guseinova; T. Sh. Shihnabieva; N. M. Bulaeva (Юг России: экология, развитие, 2015)
Development of expert systems is necessary for realization of effective ecological monitoring an environment. By development of expert systems there is a line of the problems connected to representation, processing and use received the geochemical data. In our work some approaches of the decision of the given problem which we sell with use of adaptive semantic models are offered.